Penyimpangan Kepribadian Tokoh Utama Firdaus dalam Novel Perempuan di Titik Nol Karya Nawal El-Sadaawi: Kajian Psikologi Kepribadian Alfred Adler - -, Thohari (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
Humans are social beings who have a variety of traits, characters and behaviors. Human personality is influenced by himself or another individual around him which results in their behavior of daily life. The purpose of this research using qualitative descriptive method using Alfred Adler's theory of personality psychology is to describe: (1) personality deviations of the main character in the novel Perempuan di Titik Nol by Nawal el-Sadawi, (2) factors causing the personality deviation of the main character in the novel Perempuan di titik nol by Nawal el - Sadawi. The data collection techniques used in this research are (1) literature study (2) documentation study. the results of research analysis show that various personality conflicts and psychological pressures experienced by Firdaus causes major changes in the main character, various behavioral deviations resulting in fundamental changes in the character of the main character which will last until the end of his life.